Tuesday, 31 October 2023

Tao Analysis I - 3.1.9

Exercise 3.1.9

Let A, B, X be sets such that AB=X and AB=. Show that A=XB and B=XA.


Show that A=XB

Let's start by writing down the meaning of AB=X,

xX(xA)(xB)

and also the meaning of AB=,

¬x[(xA)(xB)]

This is saying that there is no x that is in both A and B. We can write this as two separate statements,

xAxB

xBxA


Now, let's consider A.  From xX(xA)(xB), we have

xAxX

And we already have

xAxB

These two statements are both be true, so we can write them as

xA(aX)(xB)

This gives us AXB


We need to show XBA. Let's consider XB,

(xX)(xB)

Using xX(xA)(xB), we have two cases,  at least one of which is true,

  • xXxA
  • xXxB

The first case gives us

(xX)(xB)(xA)(xB)(xA)

which confirms XBA.

The second case gives us

(xX)(xB)(xB)(xB)

which is a contradiction, meaning only the first case is true.

So having shown both AXB, and XBA, we can conclude A=XB.


Show that B=XA

We could prove this using the same logic as above, or we could simply use symmetry to argue that interchanging the variables A and B doesn't change the given information and constraints (because union and intersection are commutative), but does lead the desired conclusion.


Tao Analysis I - 3.1.8

Exercise 3.1.8

Let A, B be sets. Prove the absorption laws A(AB)=A and A(AB)=A.


Show A(AB)=A

Let's write out the LHS using the definitions of intersection and union (Definition 3.1.22, Axiom 3.5).

x(A(AB))(xA)((xA)(xB))

This tells us the following two statements are both true:

  • (xA)
  • (xA)(xB)

Both statements are only true when (xA). So we can say A(AB)A.

We now need to show AA(AB)

xAxAB

This is because, by definition, AAX for any X

Furthermore, since xA is true, we have

xA(xA)(xAB)

This is equivalent to AA(AB).

Having shown both  A(AB)A and AA(AB), we can conclude A(AB)=A.


Show A(AB)=A

Let's write out the LHS using the definitions of union and intersection.

x(A(AB))(xA)((xA)(xB))

This tells us that either, or both, of the following two statements are true:

  • (xA)
  • (xA)(xB)

These become two cases to consider. 

In the first case, (xA), so A(AB)A.

In the second case, (xA)(xB)(x \in A),soagainA \cup (A \cap B) \implies A$.

Both cases gives us A(AB)A.

We now need to show AA(AB). This is straight forward, because AAX for any X, by definition. So we have  AA(AB).

So having shown both A(AB)A and AA(AB), we can conclude A(AB)=A.


Note

The proof of the first identity can be shorted as follows:

Let's write out the LHS using the definitions of intersection and union (Definition 3.1.22, Axiom 3.5).

x(A(AB))(xA)((xA)(xB))

This tells us the following two statements are both true:

  • (xA)
  • (xA)(xB)

Both statements are only true if and only if (xA). That is,

(xA)((xA)(xB))(xA)

So we can say A(AB)=A.


Monday, 30 October 2023

Tao Analysis I - 3.1.7

Exercise 3.1.7

Let A, B, C be sets. Show that ABA and ABB. Furthermore, show that CA and CB if and only if CAB. In a similar spirit, show that AAB and BAB, and furthermore that AC and BC if and only if ABC.


Show ABA and ABB

Let's start with Definition 3.1.22 of intersection,

x(AB)(xA)(xB)

Both (xA) and (xB) are true. This gives us

x(AB)(xA)x(AB)(xB)

This is equivalent to the two statements we want to prove ABA and ABB.


Show CA and CB if and only if CAB

Let's start by writing down the meanings of CA and CB,

(xC)(xA)(xC)(xB)

Both of these statements are true, so we have

(xC)(xA)(xB)

This gives us (CA)(CB)C(AB).

We now need to show C(AB)(CA)(CB). Let's apply the definition of intersection to C(AB)

xCx(AB)(xA)(xB)

This gives us two statements which are true,

(xC)(xA)(xC)(xB)

This is equivalent to C(AB)(CA)(CB).

Having shown both

(CA)(CB)C(AB)

and

C(AB)(CA)(CB)

we can conclude 

(CA)(CB)C(AB)


Show AAB and BAB

The definition of union, Axiom 3.5, tells us that xXx(XY) for any Y

So we have

xAx(AB)xBx(AB)

This immediately gives us AAB and BAB.


Show AC and BC if and only if ABC

Let's start by writing down the meanings of AC and BC,

(xA)(xC)(xB)(xC)

Either, or both, statements (xA) and (xB) implies (xC), which we write as

(xA)(xB)(xC)

This is equivalent to (AC)(BC)(ABC).

We need to show also (ABC)(AC)(BC). Let's apply the definition of union,

(xA)(xB)xC

This tells us that either, or both, (xA)(xC) and (xB)(xC) are true. That is, (AC)(BC).

Having shown both

(AC)(BC)(ABC)

and

(ABC)(AC)(BC)

we can conclude

ACBCABC

Sunday, 29 October 2023

Tao Analysis I - 3.1.6

Exercise 3.1.6

Prove Proposition 3.1.27. (Hint: one can use some of these claims to prove others. Some of the claims have also appeared previously in Lemma 3.1.12.)

Let's write out Proposition 3.1.27.

Proposition 3.1.27 (Sets form a boolean algebra). Let A, B, C be sets, and let X be a set containing A, B, C as subsets.

(a) (Minimal element) We have A=A and A=.

(b) (Maximal element)We have AX=X and AX=A.

(c) (Identity) We have AA=A and AA=A.

(d) (Commutativity) We have AB=BA and AB=BA.

(e) (Associativity) We have (AB)C=A(BC) and (AB)C=A(BC).

(f) (Distributivity) We have A(BC)=(AB)(AC) and A(BC)=(AB)(AC).

(g) (Partition) We have A(XA)=X and A(XA)=.

(h) (De Morgan laws) We have X(AB)=(XA)(XB) and X(AB)=(XA)(XB).


Let's prove each in turn.


(a) Minimal Element

We need to show A=A and A=.


Let's start with the first and use the definition of a pairwise union, Axiom 3.5.

x(A)(xA)(x)

The definition of an empty set, Axiom 3.5, tells us that an empty set has no members. That is, x is never true. So the above simplifies to

x(A)(xA)

Thus A=A.


Now let's consider A= and use the definition of intersection, Definition 3.1.22.

x(A)(xA)(x)

The definition of an empty set, Axiom 3.5, tell us that an empty set has no members. So the expression (xA)(x) is always false. That is, x(A) is never true. 

Thus A=.


(b) Maximal Element

We  need to show AX=X and AX=A.


We have already shown in Exercise 3.1.5 that AB, AB=B, AB=A are logically equivalent. Here we have AX and so AX=X, AX=A are true.


(c) Identity

We need to show AA=A and AA=A.


Let's use the definition of a pairwise union, Axiom 3.5, and equate A=B.

x(AA)(xA)(xA)(xA)

This gives us AA=A.


Now let's use the definition of intersection, Definition 3.1.22, and equate A=B.

x(AA)(xA)(xA)(xA)

This gives us AA=A.


(d) Commutativity

We need to show AB=BA and AB=BA.


Let's use the definition of a pairwise union, Axiom 3.5.

x(AB)(xA)(xB)(xB)(xA)

The second line is justified because logical disjunction is commutative.

So we have  AB=BA.


Now let's use the definition of intersection, Definition 3.1.22.

x(AB)(xA)(xB)(xB)(xA)

The second line is justified because logical conjunction is commutative.

So we have  AB=BA.


(e) Associativity

We need to show (AB)C=A(BC) and (AB)C=A(BC).


The first identity that union is associative is Lemma 3.1.12 proven in the text. 


Now we turn to the second identity (AB)C=A(BC). Using Definition 3.1.22 of intersection,

x(AB)C(xAB)(xC)

This gives us xC.

Considering (AB),

x(AB)(xA)(xB)

This gives us xA and xB.

So in summary we have that all xA,  xB and xC are true.

Using xB and xC, and Definition 3.1.22 of intersection,

(xB)(xC)x(BC)

And using xA,

(xA)(xBC)xA(BC)

That is, (AB)C=A(BC).


(f) Distributivity

We need to show A(BC)=(AB)(AC) and A(BC)=(AB)(AC).


Let's start with the first identity, and use Definition 3.1.22 of intersection,

x(A(BC))(xA)(x(BC))

This gives us xA as true, as well as x(BC).

Consider (BC) and use the definition of a pairwise union, Axiom 3.5,

x(BC)(xB)(xC)

This gives us two combinations, at least one of which must be true

  • (xA)(xB)
  • (xA)(xC)

"At least one of which must be true" means a disjunction between the two statements.

x(A(BC))(xAxB)(xAxC)

This proves the first identity A(BC)=(AB)(AC). .


Now let's consider the RHS of the second identity, and use Definition 3.1.22 of intersection,

x((AB)(AC))(x(AB))(x(AC))

Applying the definition of union Axiom 3.5, we have two combinations, both of which must be true

  • xAxB
  • xAxC

If xA then both of these statements are true. If xA, then both statements are only true if xB and xC.  That is, (xA)((xB)(xC)).

So we have shown, A(BC)=(AB)(AC).


(g) Partition

We need to show A(XA)=X and A(XA)=.


Let's start with the first identity A(XA)=X, and use Axiom 3.5 which defines union,

x(A(XA))(xA)(xXA)

Since AX, we have xAxX, which gives us

x(A(XA))(xX)(xXA)xX

The last step is true because xX is true, or xXA is true, and in both cases xX.

So we have A(XA)X. We now need to show XA(XA).

Consider xX. Since AX, we have (xA)(xA). The case (xA) combined with xX, which is true by hypothesis, gives us (xXA). So we have

xX(xA)(xXA)

That is, XA(XA)

Having shown both A(XA)X, and  XA(XA), we can conclude A(XA)=X.


Now let's consider the second identity A(XA)=, and use Definition 3.1.22 of intersection,

x(A(XA))(xA)(xXA)

So both (xA) and (xXA) must be true. However, Definition 3.1.26 for set difference tells us that (xXA) means (xA). The only solution to this apparent contradiction is if x

So we have A(XA)=.


(h) De Morgan's Laws

We need to show X(AB)=(XA)(XB) and X(AB)=(XA)(XB).


Let's start with the first identity X(AB)=(XA)(XB), and use the Definition 3.1.26 for set difference.

x(X(AB))(xX)(x(AB))

Both statements (xX) and (x(AB)) must be true. Let's consider the second statement.

(x(AB))¬((xA)(xB))(xA)(xB)

This is because ¬(PQ)(¬P)(¬Q).

We can write these as two combined statements, both of which must be true.

  • (xX)(xA)
  • (xX)(xB)

Which is equivalent to (XA)(XB).

So we have shown X(AB)=(XA)(XB).


Now let's consider the second identity X(AB)=(XA)(XB), and use the Definition 3.1.26 for set difference.

x(X(AB))(xX)(x(AB))

Both statements (xX) and (x(AB)) must be true. Let's consider the second statement.

(x(AB))¬((xA)(xB))(xA)(xB)

This is because ¬(PQ)(¬P)(¬Q).

We can write these as two combined statements, at least one of which must be true.

  • (xX)(xA)
  • (xX)(xB)

Which is equivalent to (XA)(XB).

So we have shown X(AB)=(XA)(XB).

Monday, 16 October 2023

Tao Analysis I - 3.1.5

Exercise 3.1.5

Let A, B be sets. Show that the three statements AB, AB=B, AB=A are logically equivalent (any one of them implies the other two).


Approach

There are three statements we need to show are equivalent. 

  • S1:AB
  • S2:AB=B
  • S3:AB=A

To show an equivalence between two statements SiSj we need to show SiSj and SjSi. This would suggest showing six implications in total. However, we only need to show the following three implications:

  • S1S2
  • S2S3
  • S3S1
This is equivalent to showing equivalence amongst all S1, S2 and S3, because there is a chain of implications between any Si and Sj, and also Sj and Si. For example S1S2 and S2S3S1.


Show S1S2

Using AB, we need to show both ABB and BAB.


Let's start with the definition of AB

x(AB)(xA)(xB)

By hypothesis we have AB, which is defined as

(AB)[(xA)(xB)]

Or more simply, whenever we have xA, we can substitute xB.

So, substituting into the definition of union, we have

x(AB)(xA)(xB)(xB)(xB)xB

So ABB if we're given AB.


Now we need to show BAB. Let's consider

(xA)(xA)(xB)

This is true by definition of disjunction. In fact (xA)(xA)(xC) for any C.

So BAB. Notice we didn't need to use AB here.


We have shown both ABB and BAB, from which we conclude AB=B. So ABAB=B.


Show S2S3

Using AB=B, we need to show AB=A. To do this we need to show both ABA and AAB.


Let's start with the definition of AB.

x(AB)(xA)(xB)(xA)

Thus ABA.


Now let's show AAB.

Using the definition of disjunction, we have AAB. But by hypothesis, AB=B, so we have recovered S1:AB.

Now let's consider the following which looks obvious,

(xA)(xA)(xA)

Using  S1:AB, that is (xA)(xB), we can substitute xB for xA,

(xA)(xA)(xB)

That is, AAB.


We have shown both ABA, and AAB, from which we conclude AB=A.


Show S3S1

Using AB=A, we need to show AB. This is not an equality so we don't need to show BA, which is, in any case, false.

Using the hypotheses A=AB, we immediately have

(xA)(xA)(xB)(xB)

That is AB.


Conclusion

We have shown the three implications, 

  • S1S2
  • S2S3
  • S3S1

Thereby we have shown the three statements AB, AB=B, AB=A are logically equivalent. 

Tuesday, 10 October 2023

Tao Analysis I - 3.1.4

Exercise 3.1.4

Prove the remaining claims in Proposition 3.1.17

Let's write out Proposition 3.1.17.

Proposition 3.1.17 (Sets are partially ordered by set inclusion). Let A, B, C be sets. If AB and BC then AC. If AB and BA, then A=B. Finally, if AB and BC then AC.

Note: the symbol means proper subset, that is subset but not equal.

The textbook proofs the first claim. We'll prove the remaining two.


Show that if AB and BA, then A=B

Let's write out the antecedent of this claim

(AB)(BA)

If xA then by (AB) we have xB. Similarly, if xB then by (BA) we have xA.

So we have the following

(xAxB)(xBxA)

That is,

xAxB

This is simply stating that A=B by Axiom 3.2 which defines equal sets. Thus we have shown that if AB and BA, then A=B.


Show that if AB and BC then AC

To show AC we need to show

  • if xA then xC, that is AC
  • but there exists a yC that is not in A, that is AB

Let's start with the first statement. If xA then by AB we have xB. Also, if xB then by BC we have xC. So xAxC.

Now let's address the second statement. BC tells us that there exists a yC that is not in B. But AB tells us every element xA is also in B. So every xA is in B but not every yC is in B. That is, there exists a yC that is not in A.

We have shown  AB and BC then AC.

Saturday, 7 October 2023

Tao Analysis I - 3.1.3

Exercise 3.1.3

Prove the remaining claims in Lemma 3.1.12.

Let's write out Lemma 3.1.12.

Lemma 3.1.12 If a and b are objects, then {a,b}={a}{b}. If A, B, C are sets, then the union operation is commutative (i.e., AB=BA) and associative (i.e., (AB)C=A(BC)). Also, we have AA=A=A=A.


The textbook provides a proof that union is associative. We'll prove the remaining claims.


Show {a,b}={a}{b}

Axiom 3.4 defining pair sets tells us that the only elements of {a,b} are a and b. That is

x{a,b}(x=ax=b)

Axiom 3.4 defining singletons tells us

x{a}x=ax{b}x=b

Axiom 3.5 defines pairwise union as follows

x(AB)((xA)(xB))

Thus

x({a}{b})((x{a})(x{b}))

This is equivalent to the following (Axiom 3.4),

x({a}{b})((x=a)(x=b))

And by Axiom 3.4 again,

x({a}{b})((x=a)(x=b))x{a,b}

We have shown {a,b}={a}{b}.


Union is Commutative AB=BA

We want to prove AB=BA.

By Axiom 3.5 which defines pairwise union we have

x(AB)((xA)(xB))

Because  logical disjunction is commutative, we have

((xA)(xB))((xB)(xA))

By Axiom 3.5, we also have

x(BA)((xB)(xA))

These three statements give us

x(AB)x(BA)

That is, AB=BA.


Show  AA=A=A=A

We have already shown that pairwise union is commutative, so we don't need to show again that

A=A

Let's use Axiom 3.5 which defines union to write

x(AA)((xA)(xA))

We can simplify the RHS,

x(AA)(xA)

This is simply stating that

AA=A

All that remains is to show A=A. Let's again use Axiom 3.5 which defines union to write

x(A)((xA)(x))

Since there is no x by Axiom 3.3 which defines the empty set, we can simplify the RHS,

x(A)(xA)

This is simply stating that

A=A

Tao Analysis I - 3.1.2

Exercise 3.1.2

Using only Axiom 3.2, Axiom 3.1, Axiom 3.3, and Axiom 3.4, prove that the sets , {}, {{}} and {,{}} are all distinct (i.e., no two of them are equal to each other).

Let's remind ourselves of Axioms 3.1-3.4,

  • Axiom 3.1 (Sets are objects). If A is a set, then A is also an object.
  • Axiom 3.2 (Equality of sets). Two sets A and B are equal, A=B, iff every element of A is an element of B and vice versa.
  • Axiom 3.3 (Empty set). There exists a set , known as the empty set, which contains no elements, i.e., for every object x we have x.
  • Axiom 3.4 (Singleton sets and pair sets). If a is an object, then there exists a set {a} whose only element is a, i.e., for every object y, we have y{a} iff y=a; we refer to {a} as the singleton set whose element is a. Furthermore, if a and b are objects, then there exists a set {a,b} whose only elements are a and b; i.e., for every object y, we have y{a,b} iff y=a or y=b; we refer to this set as the pair set formed by a and b.


Show is different from {}, {{}} and {,{}}.

Let's first show that is not equal to any of {}, {{}} and {,{}}

Axiom 3.3 defines the empty set as having no members. That means no element of any other set can be a member of .

The other sets do have members by Axiom 3.4. To be specific, {}{}{{}} and {,{}}

Axiom 3.2 on set equality requires equal sets to have all their members in common. So is different from all the others - because all the other sets have members, and has no members.

Having dealt with , we can now remove it from the list and consider the remaining sets {}, {{}} and {,{}}.

For the rest of this exercise we won't explicitly state that we're using Axiom 3.4 to say that a singleton set {a} has a member a, and that a pair set {a,b} has members a and b.


Show {} is different from {{}} and {,{}}.

Let's show that {} is not equal to any of {{}} and {,{}}

The element {} of {{}} is not a member of {}. Similarly, the element of {,{}} is not a member of {}. So by Axiom 3.2, {} is not equal to any of {{}} and {,{}}.

Having dealt with {}, we can now remove it from the list and consider the remaining sets {{}} and {,{}}.


Show {{}} is different from {,{}}.

Let's show that {{}} is not equal to {,{}}.

We could say the sets are not equal because their cardinalities are different. That is, |{{}}|=1 and |{,{}}|=2. However we haven't covered cardinality in the book yet so we must rely only on the Axioms 3.1-3.4, 

We can see the element of {,{}} is not a member of {{}}. So by Axiom 3.2, {{}} is not equal to {,{}}.


All the results above show that no two of the given sets are equal.

Thursday, 5 October 2023

Tao Analysis I - 3.1.1

Exercise 3.1.1

Let a, b, c, d be objects such that {a,b}={c,d}. Show that at least one of the two
statements “a=c and b=d” and “a=d and b=c” hold.


Let's start with the definition of the equality of two sets.

Axiom 3.2 (Equality of sets).Two sets A and B are equal, A=B, iff every element of A is an element of B and vice versa.

Let's apply this definition our scenario:

  1. a is a member of {c,d}. That means (a=c)(a=d) is true.
  2. b is a member of {c,d}. That means (b=c)(b=d) is true.
  3. c is a member of {a,b}. That means (c=a)(c=b) is true.
  4. d is a member of {a,b}. That means (d=a)(d=b) is true.

The key to this exercise is recognising that all four statements must be true.

Let's start by considering the case a=c, which makes (1) true. It also makes (3) true. How we ensure (2) and (4) are also true? This is only possible when b=d. Thus the statement  “a=c and b=d” satisfies the definition of set equality.

Let's consider the case a=d which makes (1) true. It also makes (4) true. How do we ensure (2) and (3) are true? This is only possible when b=c. Thus the statement  “a=d and b=c” satisfies the definition of set equality.

Can both statements be true at the same time? Let's start with a=c from the first statement. The second statement gives us b=c. The first statement then gives us b=d. That is, a=b=c=d also satisfies the equality of sets.

We have shown that the set equality {a,b}={c,d} means at least one of the statements “a=c and b=d” and “a=d and b=c” holds.